Effects of dietary metabolizable energy and crude protein levels on production performance, meat quality and cecal microbiota of Taihe Silky Fowl during growing period - Yutian Shen; Wentao Li; Lixia Kai; Yuqing Fan; Youping Wu; Fengqin Wang; Yizhen Wang; Zeqing Lu (Poultry Science)
This experiment aimed to investigate the effects of dietary metabolizable energy (ME) and crude protein (CP) levels and their interaction on the performance, meat quality, and cecal microbiota of Taihe Silky Fowl (Gallus gallus domesticus Brisson) during the growing period. A total of 2160 55-day-old Taihe Silky Fowl (half male and half female) were randomly divided into 9 groups with 6 replicates per group and 40 chickens per replicate. The fowl were fed with a 3 × 3 factor diet (ME: 11.7 MJ/kg, 12.1 MJ/kg, 12.6 MJ/kg; CP: 17.0%, 18.0%, 19.0%). The results showed as follows: with the increase of dietary ME level, the average daily feed intake (ADFI) and feed conversion ratio (FCR) of Taihe Silky Fowl during the growing period were significantly decreased (P < 0.05), reaching the lowest value in 12.6 MJ/kg group, which were decreased by 5.86% and 8.41% compared with 11.7 MJ/kg group, respectively. The dressing percentage and half-eviscerated yield rate were significantly increased (P < 0.01), with no significant difference between 12.1 and 12.6 MJ/kg groups. Dietary CP level and the interaction between ME and CP had no significant effects on growth performance, slaughter performance, organ index, serum biochemical indexes and meat quality of Taihe Silky Fowl during growing period. The richness and diversity of cecal microbiota decreased gradually with the increase of dietary ME level, and the community structure changed significantly (P < 0.05). High ME diet (12.6 MJ/kg) significantly increased the abundance of Bacteroides (P < 0.05), especially the genus Alistipes, which may indirectly improve nutrient absorption efficiency and overall health status of Taihe Silky Fowl through its metabolites and effects on intestinal microbial community structure, thereby reducing FCR. In conclusion, the optimal production performance and economic benefits can be obtained when the diet ME is 12.6 MJ/kg and CP is 17.0%.